Scaling sand dams in Southern Africa: policy guidance for optimizing rollout within an integrated water storage framework - International Water Management Institute (IWMI) (International Water Management Institute, 2025)
Southern Africa’s dryland regions face growing water insecurity due to recurrent droughts, erratic rainfall, and delayed wet seasons. Sand dams—small structures that capture and store water within sand-filled riverbeds—offer a reliable, low-maintenance source of water for domestic and productive uses in these semi-arid landscapes. Drawing on new field evidence and modelling from Zimbabwe’s Shashe catchment, this policy brief assesses sand dam performance, benefits, and enabling conditions to inform their strategic scaling.